1996
DOI: 10.1177/152660289600300407
|View full text |Cite
|
Sign up to set email alerts
|

Will it Be Feasible to Insert Endoprostheses under Interventional MRI?

Abstract: Purpose: Recent advances in magnetic resonance imaging (MRI) technology may provide a safer and more sensitive monitoring modality than X-ray imaging for endovascular surgical procedures. The purpose of this study was to investigate the feasibility of using MRI to monitor the insertion of endoprostheses. Methods: The endoprostheses we studied were composed of a nitinol stent encased in a polyester sheath. These were characterized with four different MRI techniques: the fast spin-echo; spin-echo; gradient-recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…In those who have laboured breathing but do not require mechanical ventilation, elimination of res­piratory motion artefacts can be difficult. Moreover, real‐time monitoring of interventional procedures by MRI is currently not feasible, although an in vitro experimental study is underway 22 . Technological advances in flexible broncho­scopy, allowing downsizing of the bronchoscope and angulation of the distal tip, widen the usability of this technique in infants and children with suspected airway disorders 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In those who have laboured breathing but do not require mechanical ventilation, elimination of res­piratory motion artefacts can be difficult. Moreover, real‐time monitoring of interventional procedures by MRI is currently not feasible, although an in vitro experimental study is underway 22 . Technological advances in flexible broncho­scopy, allowing downsizing of the bronchoscope and angulation of the distal tip, widen the usability of this technique in infants and children with suspected airway disorders 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Stroman and co-workers demonstrated the feasibility of performing an MR-guided stent placement making use of a polyester sheath as a delivery device for a nitinol stent in vitro (Stroman et al 1996). Manke et al reported about the MR imaging characteristics of various stents and their delivery devices (Manke et al 2000).…”
Section: Placement Of Endoprosthesesmentioning
confidence: 99%
“…The first MR‐monitored deployment of a nitinol stent in vitro was reported in 1996 111 . Later, animal models have been used to demonstrate the feasibility of MR‐guided percutaneous angioplasty in rabbit aorta and renal artery 112,113 and pig aorta and femoral artery 114,115 .…”
Section: Interventional Mrimentioning
confidence: 99%